MANAJEMEN KONVERSI TERAS RSG-GAS BERBAHAN BAKAR SILISIDA TINGKAT MUAT TINGGI - Suparlina, Lily (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
The usage of high density fuel can extend the reactor operation up to 40 days. Designing of low to high density silicide fueled core conversion has been carried out. The management of core conversion was done gradually using 2 dimensional diffusion code Batan-FUEL. Replacement of unused fuel elements in core using fuel elements reshuffle pattern 5/1, which at the beginning of cycle there are 5 fuel elemnts and 1 control element replaced. By maintaining the existing core configuration, the core conversion can be performed through mix core of 2,96 gU/cm3 - 4,8 gU/cm3 silicide fueled with respect to reactor safety limits requirements. Therefore, the objective of this work is to design the mixed cores on the neutronic performance to achieve safely at first full-silicide core for the reactor with the high uranium meat density. In the design, safety rods were used to increase the decreasing minimum shutdown margin due to high density fuel loading. The analyses results show that silicide core conversion of 2,96 gU/cm3 to 4,8 gU/cm3 density can be performed by means of indirect mix core in two steps i.e. silicide of 2,96 g U/cm3 - 3,55 gU/cm3 core conversion and silicide of 3,55 gU/cm3 - 4,8 gU/cm3 conversion with good performance. The main advantage of using high density silicide fuels of 4.8 gU/cm3 than low density silicide fuels of 2.96 gU/cm3 on the RSG-GAS core is that, the operating cycle length of 18 days could be longer in order to save fuel usage.